Implementation of Project-Based Learning on Students' Critical Thinking in Mathematics Learning in The Independent Curriculum - Johan Fanani , Ahmad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to determine the effect of project implementation-based Learning on critical-thinking students learning mathematics in the Merdeka curriculum. This research includes experimental research using the Quasi-Experimental Design technique. The research design uses a Nonequivalent Control Group Design. The population in this study was all class students XI-SAINKES SMAN 2 Pare Technique Merdeka curriculum, using the cluster random sampling technique, two classes of XI-SAINKES SMAN 2 Pare were obtained with a total of 35 students in each class. This research instrument uses a critical thinking test. Meanwhile, data analysis uses the Independent Sample t-test. From the analysis results, it can be concluded that implementing Project Based Learning influences critical thinking students in mathematics learning in the independent curriculum with a calculated tvalue of 11.331 > 1.998 ttable. Where after the implementation of PjBL in class